폐림프관근종증 치험 1례 - 정수상; 박병률; 이종수; 양석숭 (Taehan Hyungbu Oekwa Hakhoe chi, 1993)
Pulmonary lymphangiomyomatosis is rare but extremely interesting condition caused by progressive widespread smooth muscle proliferation in the perilymphatic regions throughout the lungs. The patient was a 25-year-old female. She had angiofibromas in the face, and angiomyolipoma in the left kidney which was removed 5 years earlier. Three years ago she started having severe dyspnea with bilateral pneumothoraces. Treatment was initiated with bilateral closed thoracotomies followed by open thoracotomy through median sternotomy and lung biopsy, which revealed the diagnosis of pulmonary lymphangiomyomatosis. Recurrence of pneumothorax was treated by repeated chemical pleurodesis with tetracycline. She has been in good condition during medroxyprogesterone administration for 3 years.